Continuous catalytic Friedel-Crafts acylation in the biphasic medium of an ionic liquid and supercritical carbon dioxide. - Zayed, Firas; Greiner, Lasse; Schulz, Peter; Lapkin, Alexei; Leitner, Walter (Chemical Communications, 2008)
Immobilization of catalytically-active metal salts in ionic liqs., with extn. by supercrit. carbon dioxide, affords continuous Friedel-Crafts acylation, with in situ-recycling of the catalyst. [on SciFinder(R
Keywords: acylation catalyst recycling supercrit carbon dioxide ionic liq